Factor Affecting Business Performance and Competitive Advantages in Modern Retail Strore in Makassar City - Nurul Latifa Maulani; Dian A.S Parawansa; Andi Nur Baumassepe (Magister Management, Hasanuddin University, 2021)
This study aims to analyze the factors affecting business performance and competitive advantages in modern retail stores in Makassar City. The purposive sampling method was used by selecting 100 respondents who privately own a modern retail store for more than 5 years. Data were analyzed using path analysis in SPSS 21 Programs. The results found that competitive advantages had a positive and significant effect on variable market orientation, marketplace innovation, and entrepreneurial orientation factors in modern retail stores in Makassar City. Market orientation and entrepreneurial orientation are also found to impact business performance. In this study, competitive advantage can mediate the effect of market orientation and market place innovation on business performance